Disclosure of Corporate Social Responsibility in Sharia Banks in Southeast Asian Countries Based on AAOIFI Standards - Permatasari, Annisa; Suprayogi, Noven (MALIA: Journal of Islamic Banking and Finance, 2023)
This study aims to determine the effect of profitability, bank size, and age of Islamic banks on the disclosure of Corporate Social Responsibility on Islamic banks in Southeast Asian countries based on AAOIFI standards partially and simultaneously. The population used in this study are Islamic banks in Southeast Asian countries, including Brunei Darussalam, Indonesia, Malaysia, Singapore, Thailand, Vietnam, Myanmar, and the Philippines. The sampling technique was purposive sampling to obtain 18 sample Islamic banks with a total of 126 data. This study uses a quantitative method with panel data regression analysis with Eviews 10. The results of this study partially show that the profitability and size of Islamic banks are not significant in the disclosure of Corporate Social Responsibility. In contrast, the age of the bank has a positive and significant effect on corporate social responsibility disclosure. Simultaneously, profitability, bank size, and bank age significantly positively affect Islamic banks' Corporate Social Responsibility disclosure in Southeast Asian countries for 2014-2020. The implication of the findings of this study confirm that social activities in Islamic banks are activities that must be carried out and disclosed by Islamic banks so that the bank's financial performance does not influence the implementation and disclosure of social activities in Islamic banks